Тhe Bulgarian Policy in the Black Sea Region - M. G. Bistrina (Проблемы постсоветского пространства, 2019)
The policy of Bulgaria in the Black Sea region plays an important role for the future development of the country, as well as for the development of the region as a whole. The inability to develop a national strategy aggravates a number of problems in terms of the strategic use of the resources of the Black Sea, leads to enormous losses for the country. At the present time, Bulgaria is implementing a number of policies in the Black Sea region — such as energy, trade, traffic and security, protection of the surrounding environment, regional cooperation, etc. To effectively overcome the many problems in the Black Sea region, it is necessary first of all to take collective actions that will help overcome two obstacles: the EU’s interests in the Black Sea region and Bulgaria’s ability to defend its national interests, not adhering to the EU’s common policy.At the moment, the European Union is intensifying its efforts to create an effective policy in order to enter the Black Sea region and become one of the main players. We should not forget the interests of other Great Powers like Russia and The United States.